Implementasi Corporate Governance Mechanism Terhadap Kinerja Perusahaan Korporasi di Makassar - Rosdiana Thamrin (JBIMA (Jurnal Bisnis dan Manajemen), 2018)
The purpose of this study is to analyze the influence of corporate governance mechanism on the performance of corporate corporations in Makassar. This research according to the level of exploration is included in causality research. This study uses purposive sampling technique. The type of sample used is the non-probability sampling method. The results of the study explain that (1) board characteristics variables have a positive and significant effect on company performance, (2) the audit committee has a positive and significant effect on the company's performance.